Cross-fertilization of ideas in Collective Intelligence Model (CIM) - Gunasekaran S.S.; Mostafa S.A.; Ahmad M.S.; Tang A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Intelligent agents; Robotics; Argumentation; Collective intelligences; Cross fertilization; Idea; Knowledge; Negotiation; Multi agent systems